2013
DOI: 10.1097/mlr.0b013e31829fa90d
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Patient Perceptions of Stigma in Health Care Contexts

Abstract: These findings provide insight into transgender patients' perceptions of and sensitivity to mistreatment in health care contexts. This information might be used to increase providers' cultural competency and inform their interactions with transgender patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(158 citation statements)
references
References 6 publications
1
140
1
6
Order By: Relevance
“…Transgender individuals consistently report high rates of depression, anxiety, posttraumatic stress disorder, and substance abuse (Bockting et al, 2013;Kosenko et al, 2013) compared to the general population. Multiple studies of transgender people have found high rates of suicidal ideation and attempts (Edelman et al, 2015;Grant et al, 2011;Reisner, White, Bradford, & Mimiaga, 2014).…”
Section: Psychosocial Risks and Related Health Concerns Among Transgementioning
confidence: 99%
See 3 more Smart Citations
“…Transgender individuals consistently report high rates of depression, anxiety, posttraumatic stress disorder, and substance abuse (Bockting et al, 2013;Kosenko et al, 2013) compared to the general population. Multiple studies of transgender people have found high rates of suicidal ideation and attempts (Edelman et al, 2015;Grant et al, 2011;Reisner, White, Bradford, & Mimiaga, 2014).…”
Section: Psychosocial Risks and Related Health Concerns Among Transgementioning
confidence: 99%
“…Transgender individuals face a variety of risks for discrimination, harassment, and violence that impact their psychosocial well-being and physical health (Bockting, Miner, Swinburne Romine, Hamilton, & Coleman, 2013;Edelman et al, 2015;Grant et al, 2011;Kosenko, Rintamaki, Raney, & Maness, 2013;White Hughto, Reisner, & Pachankis, 2015). However, few studies have thoroughly examined the general physical and mental health of transgender adults (Coulter, Kenst, Bowen, & Scout, 2014;Grant et al 2011; Institute of Medicine [IOM], 2011; MacCarthy, Reisner, Nunn, Perez-Brumer, & Operario, 2014).…”
Section: Colorado (Usa) By Race and Incomementioning
confidence: 99%
See 2 more Smart Citations
“…Transgender patients must also deal with the use of noninclusive language, errors in pronoun use, and the difficulties associated with filling out medical forms based on traditional gender identities. 6,7 Given these barriers experienced by transgender patients, there is a significant need to educate future healthcare providers about their specific needs. Medical and nursing schools have begun to realize the need to reevaluate their curricula 8,9 and to assess their students' attitudes.…”
Section: Introductionmentioning
confidence: 99%